Цивілізаційні виміри геоекономічних трансформацій - Кібальник, Л.О. (Культура народов Причерноморья, 2013)
Цивілізаційний характер проблем, що постають перед людством є однією з головних
характеристик економічного розвитку світового господарства. Це змушує у процесі його дослідження
використовувати цивілізаційні виміри та підходи. Така методологія дає можливість здійснити
ґрунтовний аналіз сучасних геоекономічних трансформацій світового простору та розробити
відповідний інструментарій. Найбільш доцільним є використання багаторівневого підходу щодо аналізу
геоекономічних трансформацій, а саме: філософського, загальнонаукового, конкретнонаукового та
технологічного. Цивилизационный характер пробле0м, стоящих перед человечеством является одной из
главных характеристик экономического развития мирового хозяйства. Это требует в процессе его
исследования использовать цивилизационные измерения и подходы. Такая методология позволяет
осуществить основательный анализ современных геоэкономических трансформаций мирового
пространства и разработать соответствующий инструментарий. Наиболее целесообразным является
использование многоуровневого подхода к анализу геоэкономических трансформаций, а именно:
философского, общенаучного, конкретнонаучного и технологического.
Ключевые слова. геоэкономические трансформации, геоэкономический Civilization nature of the challenges faced by humanity is one of the main characteristics of the
global economic development. This leads to using civilization dimensions and approaches in the process of its
research. Such a methodology makes it possible to carry out a detailed analysis of current geo-economic
transformation of the global space and develop appropriate analysis tools. Multilevel approach to the analysis
of geo-economic transformations, namely: philosophical, scientific (both - general and specific), and
technological is the most expedient one.
Among the methodological levels of geo-economic transformations analysis a specifically-scientific approach,
namely, its civilization component, is one of the most important. Civilization approach explains the geoeconomic
transformation as dramatic quantitative and qualitative changes that lead to the emergence of new
civilizations, recessions and the sublime, the collapse or merger, and even the disappearance of such. In terms of
a methodological approach, geo-economic transformations should be viewed as some changes in civilizations,
their interactions and dynamic relationships among them. Tracking these transformations in the global level is
made possible only through the changes in the ratio of economic power among different civilizations in such
components of the global space as: industrial, technological, financial, and ethnic.